2016
DOI: 10.1007/s11999-015-4453-0
|View full text |Cite
|
Sign up to set email alerts
|

CT-based Structural Rigidity Analysis Is More Accurate Than Mirels Scoring for Fracture Prediction in Metastatic Femoral Lesions

Abstract: Background Controversy continues regarding the appropriate assessment of fracture risk in long bone lesions affected by disseminated malignancy. Questions/purposes The purpose of this ongoing Musculoskeletal Tumor Society-sponsored, multi-institutional prospective cross-sectional clinical study is to compare CT-based structural rigidity analysis (CTRA) with physician-derived Mirels scoring for predicting pathologic fracture in femoral bone lesions. We hypothesized CTRA would be superior to Mirels in predicting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
72
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(73 citation statements)
references
References 30 publications
1
72
0
Order By: Relevance
“…2). 13 Although the future of fracture risk analysis is CT-based, 14 the axial cortical involvement is the most practical tool to use if only conventional radiographs are available.…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
“…2). 13 Although the future of fracture risk analysis is CT-based, 14 the axial cortical involvement is the most practical tool to use if only conventional radiographs are available.…”
Section: Diagnosis and Evaluationmentioning
confidence: 99%
“…We use quantitative measures of FDG avidity to identify subsequent fracture risk. For the most commonly used measure of FDG avidity, SUVmax, sensitivity and specificity of 58% and 85% were achieved, respectively, better than reported values for Mirel’s criteria [810]. For the volumetric measurement TLG, which accounts both for size and intensity of FDG-avidity, sensitivity and specificity were 85% and 80%.…”
Section: Discussionmentioning
confidence: 75%
“…Pathological fracture risk is often estimated using Mirel’s scoring [7], which combines the use of radiographs to grade size, location, and radiopacity of metastases, as well as the patient’s level of pain, to determine a composite score up to 12. Mirel’s scores of 9 or above suggested high fracture risk in initial reports [7], however subsequent evaluations found that the specificity of Mirel’s scoring is only 35–50% [810]. Accordingly, better prediction of pathological fracture risk is needed.…”
Section: Introductionmentioning
confidence: 99%
“…The orthopaedic surgeon must be able to decide whether or not to operate on a patient with metastatic disease without pathologic fracture. Several clinical scoring systems and imaging-based structural rigidity analyses have been developed to assist the orthopaedic practitioner predict the likelihood of fracture [19][20][21]. The wide range of surgical treatment options is beyond the scope of this conversation, but the goals of treatment should always focus on pain relief and functional optimization.…”
Section: Extremity Pain and Lytic Bone Lesionsmentioning
confidence: 99%